Analisis Factory Overhead Cost Dan Direct Labor Cost Dalam Menetapkan Cost Of Goods Manufactured Pada Ukm Kube Jasmine - Baru Harahap; Syahril Effendi (LPPM Universitas Putera Batam, 2022)
The purpose of this study was to find out whether the Factory Overhead Cost and direct labor costs had an effect on the increase in production. In this quantitative research two types of variables are used, namely the independent variable is Raw Material Cost, Direct Labor Cost and the dependent variable is Increased Production Results. Sampling is done by the technique used, namely purposive sampling. Data analysis using Classical Assumptions and Multiple Linear Regression methods. The results of the study were processed using SPSS 26, it can be seen that the Raw Material Cost has a tcount of 5.728 with a significance probability of 0.000, concluded that Factory Overhead Cost partially have a positive and significant effect on Increasing Production Cost of Direct Labor Costs has t count of 6.837 with a significance of 0,000 can be concluded that Direct Labor Costs partially have a positive and significant effect on Increasing Production Results. The F test shows the Fcount value of 71,270 and significance of 0,000b means that there is a significant effect between Factory Overhead Cost and Direct Labor Costs on Increasing Production Results